PENGARUH KEPEMIMPINAN DAN PENGAWASAN TERHADAP DISIPLIN KERJA PADA DINAS KETENAGAKERJAAN KOTA BIMA - Mardiana Mardiana; Sri Ernawati (LP2M Universitas Bina Bangsa, 2022)
This study aims to determine the Effect of Leadership and Supervision on Work Discipline at the Manpower Office of Bima City. The research method used is a survey method using a questionnaire distributed to 43 samples. While the instrument quality testing techniques include validity and reliability tests. The classical assumption test technique uses normality test, multicollinearity test, and heteroscedasticity test. As for testing the hypothesis using multiple linear regression analysis, t test (partial), and f test (simultaneous). The results showed that the Leadership variable (x1) had a significant influence on work discipline (y) as evidenced by the correlation coefficient of the leadership variable (x1) with an rcount test value of 0.490 > rtable 0.300, while the supervisory variable (x2) had an rcount of 0.490 which the value is greater than rtable 0.300. This proves that there is a significant influence between supervision (x2) on work discipline (y). based on the f test shows that the probability value < 0.05, it can be said that there is a significant influence jointly between the independent variables on the dependent variable. This means that there is a positive influence between leadership (x1) and supervision (x2) on work discipline (y). The conclusion of the study is based on calculations, there is a significant influence between leadership and supervision on work discipline. Based on the results of the analysis, it can be concluded that together leadership and supervision have a significant positive influence on work discipline in the Bima City Manpower Office